KDM1A inhibition augments the efficacy of rapamycin for the treatment of endometrial cancer. (1st January 2022) - Venkata, Prabhakar Pitta; Chen, Yihong; Alejo, Salvador; He, Yi; Palacios, Bridgitte E.; Loeffel, Ilanna; Liu, Junhao; Pratap, Uday P.; Gray, Gabrielle; Achuthan Pillai, Sureshkumar Mulampurath; Zou, Yi; Lai, Zhao; et al.
Abstract: Endometrial cancer (EC) often exhibit aberrant activation of PI3K/Akt/mTOR signaling and targeted therapies using mTOR inhibitors showed limited success. The epigenetic modifier, lysine-specific histone demethylase-1A (KDM1A/LSD1) is overexpressed in EC, however, the mechanistic and therapeutic implications of KDM1A in EC are poorly understood. Here, using 119 FDA-approved drugs screen, we identified that KDM1A inhibition is highly synergistic with mTOR inhibitors. Combination therapy of KDM1A and mTOR inhibitors potently reduced the cell viability, survival, and migration of EC cells. Mechanistic studies demonstrated that KDM1A inhibition attenuated the activation of mTOR signaling cascade and abolished rapamycin induced feedback activation of Akt. RNA-seq analysis identified that KDM1A inhibition downregulated the expression of genes involved in rapamycin induced activation of Akt, including the mTORC2 complex. Chromatin immunoprecipitation experiments confirmed KDM1A recruitment to the promoter regions of mTORC2 complex genes and that KDM1A inhibition promoted enrichment of repressive H3K9me2 marks at their promoters. Combination therapy of KDM1A inhibitor and rapamycin reduced the tumor growth in EC xenograft and patient derived xenograft models in vivo and patient derived tumor explants ex vivo . Importantly, in silico analysis of TCGA EC patients data sets revealed that KDM1A expression positively correlated with the levels of PI3K/Akt/mTOR genes. Collectively, our results provide compelling evidence that KDM1A inhibition potentiates the activity of mTOR inhibitors by attenuating the feedback activation of Akt survival signaling. Furthermore, the use of concurrent KDM1A and mTOR inhibitors may be an attractive targeted therapy for EC patients. Highlights: From the drug screen, we found that KDM1A inhibition is highly synergistic with mTOR inhibitors. KDM1A inhibition attenuated the mTOR signaling cascade and abolished rapamycin induced feedback activation of Akt. KDM1A is recruited to the promoters of mTORC2 complex genes and KDM1A inhibition caused enrichment of repressive histone methyl marks to reduce their expression. KDM1A inhibitor and rapamycin combination reduced the tumor growth in primary patient derived explant (PDEX), EC xenograft, and PDX models.